SOCIAL MEDIA MARKETING MODEL BASED ON EMOTIONAL ATTACHMENT AND BRAND STORY THROUGH E-WORD OF MOUTH - Mutqi Sopiawadi; Tigin Lugiani; Suci Maharani (STIESA Press, 2023)
The topic of this study is a study of the marketing activities of companies that adopt social media marketing, and how emotional attachment activities that usually can only be facilitated by service personnel and how they can influence brand stories through eword of mouth where there is still little research with the research model.To find theoretical gaps on the topics surrounding this study, the authors have studied 104 articles in journals. Conceptual references to definitions, dimensions and indicators are 56 articles and references to partial proving of relationships between variables that approach the topic of this study are 48 articles. By filtering similar research variables, only 26 articles. Then re-filtered with exactly the same variables (SMM, EA, EWOM, BS) only 15 articles which only explained the partial relationship between the variables and none of them have formed a social media marketing model based on emotional attachment and brand story through the eword of mouth. Although there is 1 journal that has a somewhat similar research model, namely (Hudson, Huang, Roth, & Madden, 2016) but with 2 different variables. So there is a theoretical gap where there has been no research with a social media marketing model based on emotional attachment and brand story through an eword of mouth with an analysis unit in the marketplace industry in Indonesia, so this is behind deductively why this research is important to fill the gap.The research method used is explanatory survey. The analytical units of this study are Marketplace Industries in Indonesia and Malaysia. The data used is primary data obtained through a survey of a sample of 100 customers and partners who have become followers of official social media accounts of the Indonesian and Malaysian marketplace industries.